A 12-week multicomponent exercise program enhances frailty by increasing robustness, improves physical performance, and preserves muscle mass in older adults with HIV: MOVIhNG study - Brañas, Fátima; Díaz-Álvarez, Jorge; Fernández-Luna, Jesús; Vásquez-Brolen, Brian D.; García-Molina, Rafael; Moreno, Elena; Ryan, Pablo; Martínez-Sanz, Javier; Luna, Laura; Martínez, Marta; Dronda, Fernando; Sánchez-Conde, Matilde (Frontiers in Public Health, 2024)
Background Our aim was to analyze the effects of a multicomponent exercise program (MEP) on frailty and physical performance in older adults with HIV (OAWH) since exercise can reverse frailty in the older population overall, but there is no data for OAWH. Methods A prospective longitudinal study with intervention and control group was designed. Sedentary adults 50 or over with and without HIV were included. The intervention was a 12-week home-based MEP. Dependent variables were frailty (frailty phenotype), physical performance (Senior Fitness Test), muscle mass (ASMI) by bioimpedance. Pre- and postintervention measurements were analyzed using McNemar’s test for categorical variables and the Wilcoxon signed-rank test for quantitative variables. Results 40 OAWH and 20 OA without HIV. The median age was 56.5 years. 23.3% were women. The prevalence of frailty was 6.6% with no frail HIV-negative participants. Three of the four frail HIV-participants transitioned two (50%) from frail to prefrail and one (25%) to robust after the MEP. In participants with an adherence ≥50%, physical performance was significantly improved [basal vs. 12 week]: upper extremity strength [13 (13–15) vs. 16 (15–19), p = 0.0001], lower extremity strength [13 (11–16) vs. 15 (13–16), p = 0.004], aerobic endurance [62 (55–71) vs. 66 (58–80), p = 0.005]. Participants with low adherence experienced a significant worsening in ASMI [8.35 (7.44–9.26) vs. 7.09 (6.08–8.62), p = 0.03]. Conclusion A 12-week MEP enhances frailty by increasing robustness in OAWH, and improves physical performance, and preserves muscle mass in older adults with good adherence to the MEP independently of HIV status. Clinical trial number: NCT 05435521